Kaempferol from Penthorum chinense Pursh suppresses HMGB1/TLR4/NF-κB signaling and NLRP3 inflammasome activation in acetaminophen-induced hepatotoxicity. Issue 9 (21st August 2020) - Du, Yi-Chao; Lai, Li; Zhang, Hao; Zhong, Fu-Rui; Cheng, Huan-Li; Qian, Bao-Lin; Tan, Peng; Xia, Xian-Ming; Fu, Wen-Guang
Abstract : In this study, kaempferol (KA) ameliorates APAP-induced hepatotoxicity by activating HO-1/NQO1 and inhibiting HMGB1/TLR4/NF-κB signaling and NLRP3 inflammasome activation. Abstract : Acetaminophen (APAP) is one of the safest and most effective over-the-counter (OTC) analgesics and antipyretics, but excessive doses of APAP will induce hepatotoxicity with high morbidity and mortality worldwide. Kaempferol (KA), a flavonoid compound derived from the medicinal and edible plant of Penthorum chinense Pursh, has been reported to exert a profound anti-inflammatory and antioxidant activity. In this study, we explored the protective effect and novel mechanism of KA against APAP-induced hepatotoxicity. The results revealed that KA pretreatment significantly reduced the levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), relieved hepatocellular damage and apoptosis, attenuated the exhaustion of glutathione (GSH) and accumulation of malondialdehyde (MDA), increased the expression of antioxidative enzymes ( e.g., heme oxygenase 1 (HO-1) and NADPH quinone oxidoreductase 1 (NQO1)), and thus restrained APAP-induced oxidative damage in the liver. KA suppressed the expression of NLRP3 and reduced the levels of pro-inflammatory factors, including interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). Moreover, KA remarkably inhibited high-mobility group box 1 (HMGB1) and toll-like receptor 4 (TLR4) expression as well as nuclear factor kappa-B (NF-κB) activation for liver protection against APAP-induced inflammatory responses and apoptosis. Taken together, our findings suggested that KA could effectively protect hepatocytes from APAP hepatotoxicity through the up-regulation of HO-1 and NQO1 expression, the down-regulation of NLRP3 expression, and the inhibition of the HMGB1/TLR4/NF-κB signaling pathway.